2016
DOI: 10.1080/14767058.2016.1250258
|View full text |Cite
|
Sign up to set email alerts
|

Maternal diet and breastfeeding duration of infants after NICU hospitalization in Greece: a cohort study

Abstract: Mothers who consumed the recommended by the NDG fruit servings/day breast-fed their hospitalized newborns for a longer period. Despite the fact that our participants were highly motivated and willing to breast-feed, we argue that this relationship is highly unlikely to be biological.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…19 Also, a smaller cohort study showed that intake of vegetables and fruit during lactation associated with breastfeeding duration, which may relate to improved health outcomes in infants. 20,21 However, this observed association may not imply a causal relationship. 20,21 Further differences between maternal plant-based and omnivore diet patterns, including saturated fat intake and n-6 to n-3 long chain polyunsaturated fatty acids ratio may influence growth and obesity risk of offspring.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…19 Also, a smaller cohort study showed that intake of vegetables and fruit during lactation associated with breastfeeding duration, which may relate to improved health outcomes in infants. 20,21 However, this observed association may not imply a causal relationship. 20,21 Further differences between maternal plant-based and omnivore diet patterns, including saturated fat intake and n-6 to n-3 long chain polyunsaturated fatty acids ratio may influence growth and obesity risk of offspring.…”
Section: Introductionmentioning
confidence: 83%
“…20,21 However, this observed association may not imply a causal relationship. 20,21 Further differences between maternal plant-based and omnivore diet patterns, including saturated fat intake and n-6 to n-3 long chain polyunsaturated fatty acids ratio may influence growth and obesity risk of offspring. 22,23 To the best of our knowledge, there is no study that has investigated the relationship between different maternal plant-based dietary patterns and growth of infants during lactation.…”
Section: Introductionmentioning
confidence: 83%